Professional Athletes Have Poorer Sleep Quality and Sleep Hygiene Compared With an Age-Matched Cohort. Issue 6 (November 2021) - Cameron, Alyse F. M.; Perera, Nirmala; Fulcher, Mark
Abstract : Objective: To study sleep quality and sleep hygiene in professional athletes and an age-matched cohort. Design: Cross-sectional study. Setting: Professional athletes and a sport medicine center. Participants: Professional rugby, netball and football athletes (n = 184) and attendees to a sport medicine center (n = 101). Interventions: Participants completed an online survey. Main Outcome Measures: Sleep Hygiene Index (SHI) and Pittsburgh Sleep Quality Index (PSQI). Results: Forty-five percent (n = 128) of respondents were aged between 18 and 24 years, 54% (n = 154) were men and 65% (n = 184) were professional athletes. The sleep duration of the professional athletes (mean rank 134.3, n = 181) was greater than the age-matched cohort (mean rank = 154.4, n = 101), U = 7835.0, z = −2.3, P = 0.02; however, they reported more sleep disturbance (mean ranking = 148.0, n = 181) than the age-matched cohort (mean rank = 129.8, n = 101), U = 7960.5 z = −2.5, P = 0.01, 2–tailed. Professional athletes had worse sleep regularity (mean rank = 152.3, n = 183) compared with the age-matched cohort (mean rank = 124.6, n = 101), U = 7448.5, z = −2.7, P = 0.006, 2-tailed, had an inferior sleep environment (mean rank = 149.5, n = 183) compared with the age-matched cohort (mean rank = 129.8, n = 101), U = 7959.5, z = −2.0, P = 0.047, and had more naps (mean rank = 156.2, n = 183) compared with the age-matched cohort (mean rank = 117.6, n = 101), U = 6729.0, z = −4.2, P = 0.00 0, 2-tailed. Conclusions: Professional athletes reported poorer sleep quality and sleep hygiene compared with an age-matched cohort, and difficulty falling asleep following competition. It is likely this is due to the stress of competition, training, and traveling. Because sleep plays an important role in postexercise recovery and has an impact on injury and athletic performance, it is important to have strategies to support better sleep quality and sleep hygiene in athletes. Abstract : Supplemental Digital Content is Available in the Text.